2012
DOI: 10.3892/mmr.2012.818
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of antibiotic use in the community: Νon-adherence and self-prescription rates in an Italian urban population

Abstract: Abstract. The aim of the present study was to assess the pattern of antibiotic use in a community setting of an urban area of Italy and identify factors that affect adherence to their use. By using a questionnaire-based survey, we collected 1,269 interviews and performed analysis on those patients who had their last course of antibiotic within the past 12 months (956 subjects). Among the subjects reporting that they had not followed their last antibiotic course as prescribed, 14.7% stopped therapy early, 5.4% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
3
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 20 publications
2
18
3
3
Order By: Relevance
“…Engagement with regular job was one of the predictors of inappropriate use of antibiotics in this study, which is similar to other studies [ 17 , 21 , 55 , 56 ]. The possible explanation could be due to lack of time to visit health care facilities during working hours, which may enforce to obtain antibiotics without prescription [ 55 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Engagement with regular job was one of the predictors of inappropriate use of antibiotics in this study, which is similar to other studies [ 17 , 21 , 55 , 56 ]. The possible explanation could be due to lack of time to visit health care facilities during working hours, which may enforce to obtain antibiotics without prescription [ 55 ].…”
Section: Discussionsupporting
confidence: 92%
“…The effectiveness of antibiotics is threatened by antimicrobial resistance that can arise from discontinuation of the full course of treatment [ 6 ]. Studies found that the reasons for discontinuation of antibiotics may be due to lack of knowledge and awareness regarding antibiotic use [ 21 , 52 , 53 ]. In this study, 27% of the respondents discontinued their antibiotics once the symptoms subside.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were in agreement with a previous Italian report, although at much lower incidence rates, focusing on the misuse of antibiotics. 14 It has been widely reported that the educational level of patients could influence IDU in general and was found to probably underscore polypharmacy in less-educated elderly. 23 This may emphasise the importance of setting new policies, undertaking training programs for healthcare professionals and running up IDU awareness raising campaigns directed mainly towards outpatients.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that 60.42 % of participants were university graduates, and the reason for this could be that a teaching university hospital was one of three health service providers being involved in this study, and therefore it would be expected that a high number of outpatients were postgraduate students or academic staff. It has been reported that the most commonly and inappropriately used drugs include mainly antibiotics, 14,24 as well as analgesics, antidepressants and anticholinergic drugs especially in the elderly. 12 IDU does have morbidity and mortality consequences 1 and is associated with increased rates of adverse drug reactions 25-27 and increased bacterial resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation